PENDIDIKAN TAREKAT DI SURAU QAWIYYUL AMIN KABUPATEN ROKAN HULU - ', Sutiarto; Achmad, Said Suhil; ', widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is based on the difference of education in every tarekat surau in Rokan Hulu regency. The formulation of this research problem is how about this prosess of education tarekat in Surau Qawiyyul Amin Rokan Hulu regency ?. The purpose of this research is to know the form of education in Surau Qawiyyul Amin Rokan Hulu district. Informants in this study are the researchers themselves and respondents as many as 3 people who have been selected by researchers. The sample used is propoersive sampling. This research instrument uses interview, observation and documentation. The result of the analysis that can be drawn conclusion of tarekat education process in Surau Qawiyyul Amin is done by doing orientation period, then bai'at, then follow the routine activity of charity weekly (wirid).Keywords: education, tarekat in Surau Qawiyyul Amin